Efforts To Improve Children’s Cognitive Abilities Through Playing Puzzle Activities in Group B At Kindergarten Satap Fatumuti - Yasinta Taolin; Novilia Devi Dewitanty (Early Childhood Education Development and Studies (ECEDS), 2022)
This research was conducted to address the problem of improving children's cognitive abilities through puzzle playing activities. This study aims to improve children's cognitive abilities through playing puzzle activities at TK Satap Fatumuti group B in 2021. This research was carried out using Classroom Action research which consisted of two cycles, with five meetings in each cycle. This research was conducted for approximately two weeks. The results of the study proved that through playing puzzles children could improve their cognitive abilities at each meeting, the cognitive ability of children in cycle one was 30% with very poor criteria and in the second cycle it increased to 70% with very good criteria. Every time it is carried out in cycle one and cycle two it can be concluded that in learning improvement activities the cognitive abilities of group B TK Satap Fatumuti have increased. The teacher is a model, motivator, facilitator for their students. Teachers should continue to explore and develop their abilities to improve children's cognitive abilities in optimal and varied puzzle playing activities.